An example of prompt and appropriate multidisciplinary management leading to an exceptionally good outcome: a case complicated by amniotic fluid embolism. (24th November 2015) - Patel, Deesha; Osakwe, Osaeloke; Ghosh, Sayanti
Abstract : Amniotic fluid embolism (AFE) is a rare and serious phenomenon; we describe a rare case of AFE occurring after a second trimester surgical termination in a private clinic, which, with prompt transfer and appropriate multidisciplinary management, had an exceptionally good outcome. The patient developed hypotension, respiratory arrest and disseminated intravascular coagulopathy following the procedure but with aggressive management she made a full recovery without any neurological or long-term sequelae.